A Combination of a Volatile‐Memristor‐Based True Random‐Number Generator and a Nonlinear‐Feedback Shift Register for High‐Speed Encryption. (5th March 2020) - Woo, Kyung Seok; Wang, Yongmin; Kim, Yumin; Kim, Jihun; Kim, Woohyun; Hwang, Cheol Seong
Abstract: A true random‐number generator (TRNG) and a nonlinear feedback shift register (NFSR) are combined to create a new type of TRNG. This TRNG is based on the intrinsic stochasticity of threshold switching behavior in a Pt/HfO2 /TiN memristor and an NFSR circuit. Considering the transition rate of the hopping process, the stochasticity of the delay time can be attributed to the phonon‐assisted hopping process. This novel TRNG passes all 15 National Institute of Standards and Technology randomness tests without post‐processing steps, proving its performance as a hardware security application. By combining the TRNG with the NFSR, the bit generation rate is further improved, allowing it to be used for high‐speed applications. Abstract : A true random‐number generator (TRNG) and a nonlinear feedback shift register (NFSR) are combined to create a new type of TRNG. This TRNG is based on the intrinsic stochasticity of threshold switching behavior in a Pt/HfO2/TiN memristor and an NFSR circuit. The bit generation rate is further improved, allowing it to be used for high‐speed applications.